2001
DOI: 10.1002/1521-396x(200103)184:1<263::aid-pssa263>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effect on GaN Buffer Layer Surface

Abstract: We investigate the effect of annealing parameters (carrier gas, duration) on GaN buffer layers grown by metalorganic vapor phase epitaxy. The samples were characterized in situ by a laser reflectometry (LR) set-up with a He-Ne laser beam and ex situ by atomic force microscopy (AFM). The reflectivity decreases when the temperature is about 1050 C. This fact depends on the hydrogen flow rate in the H 2 þ N 2 gas mixture and the thickness of the buffer layers. The correlation between this observation and the AFM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…This roughened growth mode results in an attenuation of the reflectance signal. A similar reduction in the reflectance signal due to roughness has also been observed as the NL is annealed [30,41,42]. The root-mean-square (RMS) surface roughness, s RMS , will attenuate the surface reflectivity, R, by…”
Section: Article In Presssupporting
confidence: 52%
See 3 more Smart Citations
“…This roughened growth mode results in an attenuation of the reflectance signal. A similar reduction in the reflectance signal due to roughness has also been observed as the NL is annealed [30,41,42]. The root-mean-square (RMS) surface roughness, s RMS , will attenuate the surface reflectivity, R, by…”
Section: Article In Presssupporting
confidence: 52%
“…Optical reflectance has previously been used to investigate GaN film evolution [30,[38][39][40][41][42][43][44]. In these optical reflectance studies, particular attention has been paid to the NL evolution [30,38,41,44] and the 3D roughening to 2D smoothing transition at high T [38][39][40]42,43].…”
Section: Optical Reflectance To Measure Film Roughnessmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10]), but only a few of these describe its influence on the GaN NL [11,12]. Halidou et al [11] presented AFM images of NL grown using different carrier gas. The authors observed similar relations between carrier gas and and NL surface morphology as presented in this paper.…”
Section: Introductionmentioning
confidence: 99%